SISTEM PENDETEKSI ASAP ROKOK DI RUANG KAMPUS - Utama, Hadian Satria; Nurwijayanti, Nurwijayanti; Mario, Mario (TESLA Jurnal Teknik Elektro UNTAR, 2008)
The device that designed by writer is smoke sensor device that use smoke sensor. System is controlled by microcontroller that purposed to take conversion result data from analog voltage which made by smoke sensor that converted to the digital data. The data send through microcontroller using DTMF wave to receive at monitoring room in DTMF wave shape, the receive wave will be sent to the PC and receive by Visual Basic program. The final result from this project can be use on the screen from the computer PC, the result is an voltage number detection with the sensor. If the score showing with the cigarette smoke sensor higher than limited score cigarette smoke than alarm will be work.